The Differentiation of Guarantees that are Derived from the Principle of Due Process in the Application of Administrative Sanctions - Markevičiūtė, Milda (Teisė, 2021)
The aim of this article is to analyse the origins of differentiation of guarantees that are derived from the principle of due process in regulation of administrative sanctions and the problems caused thereof. In order to reach this aim, the following objectives are established: 1) to reveal the regulation of the guarantees that are derived from the principle of due process in administrative sanctions; 2) to evaluate the validity of analysed regulations and its compatibility with applicable law; 3) to analyse the problems caused by the current legal regulation. The object of the analysis is the legal regulation of guarantees that are derived from the principle of due process int the Administrative Violations Code (AVC) and specialised laws. The factors that influenced the differentiation of guarantees that are derived from the principle of due process (or its reduction) in administrative sanctions are evaluated. The analysis revealed that the guarantees that are derived from the principle of due process are defined as lacking particularity and a proper system, incompatible with the Convention and thus inconvenient in situations when a person is charged with administrative violation.
Keywords: administrative sanctions; due process guarantees; differentiation of administrative sanctions